Politik Hukum Sistem Upah Minimum Dan Tunjangan Bagi Pekerja Rumah Tangga Di Indonesia - Moh Asman Novi Ambar (Mimbar Yustitia: Jurnal Hukum dan Hak Asasi Manusia)
The state has guaranteed the right to decent jobs and livelihoods, but formal job opportunities are insufficient. As a result, many work as domestic workers, although the regulations on their wages and benefits are still lacking. Data shows the majority of domestic workers are paid below minimum wage without benefits. This study provides an in-depth analysis of the application of laws and regulations, legal principles and doctrines related to these issues, so that it can be the basis for formulating appropriate policies for the protection of normative rights of domestic workers. This research uses a normative juridical method by examining laws and regulations as well as principles and legal doctrines related to the wages and benefits of domestic workers. This is important to formulate the right policies to protect the normative rights of domestic workers without compromising employers’ interests. Some countries like South Africa and the Philippines have provided better protection for domestic workers through specific laws. They set minimum wage standards, maternity leave rights, unemployment insurance, THR allowances, to decent housing guarantees. Indonesia also needs to revise its policies to provide decent income and benefits for domestic workers. The government is advised to set minimum wage standards for domestic workers equivalent to the provincial minimum wage along with sanctions for violations. Thus, fair and dignified arrangements for domestic workers can be realized immediately without overriding the interests of employers or employers.